IMPROVEMENT STUDENT'S LEARNING MOTIVATION AND CONCEPT MASTERY BASIC LAWS OF CHEMISTRY BY IMPLEMENTATION OF PEER LED GUIDED INQUIRY (PLGI) LEARNING - rizky dewi nursanty; ratu betta rudibyani; tasviri efkar (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
This research aimed to describe effectiveness of PLGI learning in improving of student’s learning motivation and concept mastery at Basic Laws of Chemistry.  The population in this study was all students of class X in State Senior High School 2 Gadingrejo at school year 2012-2013. Sampling use class X1 as a control class and X2as a experiment class. This is a quasi-experimental research using Non Eqiuvalent (Pretest-Posttest) Control Group Design. Effectiveness of learning was measured based on improvements n-Gain significant and students be more motivated to study hard and get a better mastery of the concept after learning.  The results showed that: (1) the average value of n-Gain student’s learning motivation in experiment class and control class are 0,14 and 0,02, and the average value of n-Gain mastery of the concept in experiment class and control class are 0,58 and 0,42.  (2) the percentage of  highly motivated students each indicator of motivation in the experiment class was higher than the control class, (3) mastery learning experiment class reached 89,29%, while the control class reached 60,71%.  Showing that student’s learning motivation and concept mastery at Basic Laws of Chemistry in experiments class were higher than the control class.  Thus, the PLGI learning model is effective in improving student’s learning motivation and mastery of the concept at basic laws of chemistry in state senior high school 2 Gadingrejo.Keywords: Peer Led Guided Inquiry, student’s learning motivation and concept  mastery